Design and Build a Facial Recognition Based Motor Vehicle Security System - Muhammad Syarif Hartawan (International Journal of Science, Technology & Management, 2022)
The background of this research is to build a system that will be able to help reduce crime, especially not the crime of motor vehicle theft by using the concept of facial recognition on every motorized vehicle. Therefore, the owner will be recognized by the vehicle directly. The method used in this study is to use the method of literature study or literature review by using the basis of journals with the same research because this will find differences between journals and other journals so as to find novelty in journal writing. The problem raised in this research is how to reduce the rate of motor vehicle theft by using the system method or the internet of think method, therefore by making this system it will be able to help the police in reducing the crime of motor vehicle theft. The purpose of making this paper is how to create a system that can reduce motor vehicle crime, especially motor vehicle theft so that it can make motorists trust in leaving their motorized vehicle anywhere. Therefore, by making a facial recognition system on vehicles it will be able to reduce crime rates and can make motor vehicle drivers believe.